A method for evaluating the plasticity of plastic fat

Monitoring the composition changes of triglycerides through transesterification technology has solved the problem that the existing technology cannot effectively evaluate the plasticity of plastic fats, real reflection of ductility and viscosity, providing a quick and simple evaluation method, and improving evaluation accuracy.

CN114689465BActive Publication Date: 2024-12-31JINAN UNIVERSITY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210422591.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-04-21
Publication Date
2024-12-31
Estimated Expiration
2042-04-21

AI Technical Summary

Technical Problem

The existing methods cannot truly reflect the ductility of plastic fat, resulting in the contradictory trends of ductile viscosity and consistency change in actual applications, and the plasticity of plastic fat cannot be effectively evaluated.

Method used

Through the transesterification technology, the changes in the content of medium melting point and high melting point triglycerides are monitored, and the percentage of the total amount of high melting point triglycerides account for the content of medium melting point and high melting point triglycerides is calculated. Combined with the viscosity and consistency characteristics, the plasticity of plastic fats is evaluated. .

Benefits of technology

The ductility and viscosity of plastic fats are achieved, providing a quick and easy way to predict plasticity, guiding the selection and modification of base oil of plastic fats, and improving the accuracy of evaluation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003608523890000041
    Figure BDA0003608523890000041
  • Figure BDA0003608523890000051
    Figure BDA0003608523890000051
  • Figure BDA0003608523890000121
    Figure BDA0003608523890000121
Patent Text Reader

Abstract

The present invention belongs to the field of light industrial oils and fats, and discloses a method for evaluating the plasticity of plastic fats by measuring the changes in triglyceride composition in plastic fats. The method comprises the following steps: adding an enzyme catalyst to a mixed oil, setting the reaction temperature and performing ester exchange modification; monitoring the content of medium melting point triglycerides and high melting point triglycerides in the system, calculating the percentage of the total amount of high melting point triglycerides in the sum of the content of medium melting point and high melting point triglycerides, and reflecting the consistency, viscosity and plasticity changes of the plastic fat through the numerical change rate. And verifying it through crystallization characteristics. The method can calculate and predict plasticity when testing the glyceride composition, and there is no need to measure its crystallization characteristics, which is easier to operate. It also provides theoretical and method guidance for the selection, compounding and modification preparation of base oils of plastic fats.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of light industrial oils and fats, and in particular relates to a method for evaluating the plasticity of plastic fat by measuring the change of triglyceride composition in the plastic fat. Background Art

[0002] Natural oils and fats are generally a mixture of solid oils and liquid oils at room temperature. Solid fat content (SFC) is an indicator of the melting and hardness performance of oils and fats at different temperatures, and is also an important indicator for food manufacturers to control quality. In the oil processing industry, SFC is often used to determine and adjust the fractionation technology of palm oil, and is also used to guide the production and processing of plastic fats such as cocoa butter, margarine, and butter. General food-specific oils and fats will consider their operating characteristics in practical applications, among which plasticity (ductility + consistency) is the basic characteristic of margarine / shortening. "Food-Specific Oils and Fats" (first edition in 2017, edited by Liu Yuanfa, China Light Industry Press) believes that the crystallization characteristics of oils and fats with good plasticity should be mainly β'. At present, the SFC curve characteristics are often used in industry to reflect the consistency of oils and fats from the side, but SFC can only reflect the ability of oils and fats to resist temperature fluctuations from the solid fat range, and cannot truly reflect the ductility of oils and fats, so it is necessary to combine viscosity for comprehensive evaluation.

[0003] At present, the development of plant-based plastic fats often uses mixed vegetable oils as the base oil. Usually, the mixed oils are transesterified to improve the consistency of the plastic fat. The traditional method of evaluating the plasticity of plastic fats is (1) judging by the SFC values ​​at different temperatures, that is, the more slowly the SFC value changes with the temperature rising, the better the consistency and plasticity of the plastic fat; (2) the relationship between the viscosity and ductility of oils and fats generally shows a positive correlation, that is, the higher the viscosity value, the better the ductility of the plastic fat when rolled by external force. However, in actual applications, sometimes there is a contradiction between the trend of ductile viscosity and consistency change. Therefore, it is necessary to provide a new method to evaluate the plasticity of plastic fats and verify it through crystallization characteristics. Summary of the invention

[0004] The plasticity of plastic fat is mainly reflected in its ductile viscosity and consistency. In order to improve the problem that the SFC curve characteristics of plastic fat cannot truly reflect the ductile viscosity of plastic fat, the primary purpose of the present invention is to provide an evaluation method that utilizes the changes in the proportion of triglyceride components containing palmitic acid, stearic acid, oleic acid, lauric acid, and myristic acid, corresponds to the actual oil SFC (20-40°C) curve consistency characteristics and ductile viscosity change results, and verifies them through crystallization characteristics to truly reflect the plasticity changes of plastic fat.

[0005] The purpose of the present invention is achieved through the following technical solutions:

[0006] A method for evaluating the plasticity change of plastic fat comprises the following steps:

[0007] (1) adding an enzyme catalyst to the mixed oil and fat, setting the reaction temperature and performing transesterification modification;

[0008] (2) The content of medium melting point triglycerides and high melting point triglycerides in the monitoring system is calculated, and the percentage of the total amount of high melting point triglycerides to the total content of medium melting point and high melting point triglycerides is calculated. The change rate of the numerical value can simultaneously reflect the changes in the consistency, viscosity and plasticity of the plastic fat.

[0009] The oil is an ester formed by higher fatty acids and glycerol. The mixed oil in step (1) is obtained by mixing an oil rich in lauric acid C12:0 (L) and myristic acid C14:0 (M), and an oil rich in palmitic acid C16:0 (P), stearic acid C18:0 (S) and oleic acid C18:1 (O). The mixed oil must contain these five fatty acids, but may not contain other fatty acids.

[0010] Preferably, in the mixed oil described in step (1), the mass percentage of lauric acid L is 1-28.6%, the mass percentage of myristic acid M is 1-10.2%, the mass percentage of palmitic acid P is 21.4-45%, the mass percentage of stearic acid S is 1-5%, and the mass percentage of oleic acid O is 26.5-40.7%, wherein the mass percentage refers to the percentage of the corresponding fatty acids in the total mass of the mixed oil after the mixed oil is completely hydrolyzed.

[0011] More preferably, the mass percentage of lauric acid L in the oil described in step (1) is 5.7-9.5%, the mass percentage of myristic acid M is 2.8-7.1%, the mass percentage of palmitic acid P is 34.5-35.9%, the mass percentage of stearic acid S is 3.5-4.3%, and the mass percentage of oleic acid O is 36.2-38.9%; in this case, it is easier to obtain plastic fat with good plasticity.

[0012] The enzyme catalyst in step (1) is low-temperature lipase, preferably one of lipase Lipozyme TL IM and lipase Lipozyme RMIM.

[0013] The amount of the enzyme catalyst added in step (1) is 3-10% of the mass of the mixed oil;

[0014] The temperature of the transesterification reaction in step (1) is 60-80° C., and the reaction time is 30-120 min.

[0015] The high melting point triglycerides described in step (2) are PPP and PPS type triglycerides, and the medium melting point triglycerides are triglycerides with a total carbon number below C46, ​​MPP and MOM type triglycerides.

[0016] In step (2), when the total amount of high melting point triglycerides accounts for the percentage of the sum of the contents of medium melting point and high melting point triglycerides in the range of 13-18%, it indicates that the plastic fat obtained has improved ductility and viscosity, improved consistency, and better plasticity relative to the mixed fat before modification; when the total amount of high melting point triglycerides accounts for the percentage of the sum of the contents of medium melting point and high melting point triglycerides <13% or greater than 18%, it indicates that the consistency of the plastic fat obtained has improved, the ductility and viscosity has decreased, and the plasticity has deteriorated, and when the total amount of high melting point triglycerides accounts for the percentage of the sum of the contents of medium melting point and high melting point triglycerides >18%, the consistency has improved more than when the percentage is <13%. The changes in viscosity and plasticity are relative to the raw material mixed fat before the esterification reaction.

[0017] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0018] The present invention provides a method for predicting plasticity by changing the glyceride composition of plastic fat before and after ester exchange, and verifies it through crystallization characteristics, proving that the method can truly reflect the application characteristics of plastic fat such as ductility and viscosity when characterizing the physicochemical properties of plastic fat, and also provides theoretical and methodological guidance for the selection, compounding and modification preparation of base oil of plastic fat.

[0019] The present invention provides a rapid method for calculating and predicting plasticity when testing the glyceride composition, without the need to measure its crystallization characteristics, so this method is simpler than crystallization testing. DETAILED DESCRIPTION

[0020] The present invention is further described in detail below in conjunction with the examples, but the embodiments of the present invention are not limited thereto. The raw materials involved in the present invention can be directly purchased from the market. For process parameters not particularly noted, conventional techniques can be used. The lipases used in the examples were purchased from Novozymes.

[0021] The present invention uses an enzyme-catalyzed transesterification of oils and fats rich in lauric acid, myristic acid, palmitic acid, oleic acid and stearic acid to monitor the content and ratio of medium- and high-melting-point triglycerides in the product during the transesterification process, thereby evaluating the plasticity and viscosity of the product and providing a new evaluation method for developing high-quality plastic fats. The experimental data and comparative test data of the evaluation method are studied in the following examples.

[0022] Example 1

[0023] 1. Preparation of transesterified oils and fats

[0024] Mixed oil (palm kernel oil with a melting point of 26°C, SFC of 10°C = 55.6, 20°C = 18.7, 25°C = 0, 30°C = 0, 35°C = 0, 40°C = 0 and palm oil with a melting point of 24°C, SFC of 10°C = 33.2, 20°C = 4.6, 25°C = 1.2, 30°C = 0.9, 35°C = 0, 40°C = 0, all purchased from Kerry Special Oils (Shanghai) Co., Ltd.) 100g, heated to melt and mixed evenly, the lauric acid L content in the mixed sample was 9.5%, the myristic acid M content was 7.1%, the palmitic acid P content was 34.5%, the stearic acid S content was 3.5%, and the oleic acid O content was 36.2%. Then put it into a reactor and set the reaction temperature to 75°C. When the temperature is constant, add 5 g of immobilized lipase Lipozyme TL IM and stir to react so that the oil and enzyme react fully. After reacting for 60 minutes, collect the oil sample as the enzymatic ester exchange oil.

[0025] 2. Test methods

[0026] (1) Analysis of triglyceride composition

[0027] Gas chromatography conditions are: capillary column RTX-65TG type (30m×0.250mm×0.1um), injection volume: 0.2uL, ion flame detector temperature: 360℃; heating program: initial temperature 250℃, hold 1min, 20℃ / min heating to 280℃, 10℃ / min heating to 340℃, hold 1min, 1℃ / min heating to 350℃, hold 20min, split ratio 50:1, carrier gas: hydrogen. If the content of medium melting point triglycerides (total TAG below C46, ​​MPP, MOM) is insufficient, the SFC at 10-25℃ will not be significantly improved. If the content of high melting point triglycerides (PPP and PPS) accounts for an insufficient proportion of the total content of medium and high melting point triglycerides, the phenomenon of insufficient SFC improvement at high temperature (30-40℃) will also occur.

[0028]

[0029] (2) Plasticity evaluation

[0030] (2.1) The consistency characteristics are expressed as solid fat content (SFC). The determination of SFC refers to AOCS Official Method Cd 16-81. Take 3 mL of oil sample in a solid fat determination tube, melt it at 60°C for 30 minutes to eliminate the crystallization memory, then transfer it to 0°C for 60 minutes, and then transfer it to 10, 20, 25, 30, 35, and 40°C for 30 minutes each to measure the SFC value at each temperature. At 20-40°C, the more slowly the solid fat changes with temperature, that is, the smaller the SFC decrease rate, the higher the consistency of the oil.

[0031]

[0032] (2.2) Ductility

[0033] The ductility is expressed as ductile viscosity, and the viscosity test is performed using a Malvern rheometer test with a shear rate of 0.1-100s. -1 .

[0034] (2.3) Plasticity verification analysis

[0035] Crystallization characteristics analysis shows that plastic fat with good plasticity is mainly β′ crystal. The sample is evenly smeared on a glass slide and aged at 20°C for 24 hours before PLM observation; the polycrystalline morphology is observed using X-rd, CuKa radiation source, λ=0.154 18nm, scanning under the working conditions of tube voltage 44kV, tube current 40mA, and the scanning range is 1-30°.

[0036] Generally, plastic fats will consider their operational characteristics in practical applications, such as plasticity that can change shape under the action of external forces. This is the basic characteristic of margarine / shortening. When preparing shortening, margarine and baked products, it is expected to obtain β'-type crystals because it can make the solidified fat soft and hard, and help a large amount of air to be stirred in in the form of small air bubbles, thereby forming a product with good plasticity and creaming properties. Therefore, in practical applications, technicians in this field generally use the β' ratio to judge plasticity ("Special Oils and Fats for Foods" 2017 first edition, edited by Liu Yuanfa, China Light Industry Press, page 168 "Margarine requires the fat crystal form to be β'", page 192 "The solid phase fat in shortening should be selected from hard fat that can form β' crystal form"). When the β' ratio is increased compared to before esterification modification, the plasticity is improved; when the β' ratio is reduced compared to before esterification modification, the plasticity is reduced;

[0037] In the product obtained in Example 1, high melting point triglycerides account for 15.3%. According to the method of the present invention, the consistency of the plastic fat is improved, the ductility and viscosity are improved, and the plasticity is improved.

[0038] It has been verified that the viscosity of the product increased from the initial (i.e., the viscosity of the mixed oil before transesterification) 103mpa·s to 968mpa·s, and the viscosity was improved; the SFC value of the mixed oil was: 10℃36.49, 20℃6.72, 25℃1.0, 30℃0.76, 35℃0, 40℃0, that is, the SFC decrease rate (%) of the mixed oil was 100%, and the SFC change trend of the product was more gentle than that of the raw material mixed oil, and the consistency was improved; the product crystallization was mainly β′ crystal (the proportion increased from 16% to 85%), and the plasticity was improved. It is consistent with the conclusion of the present invention, indicating that the evaluation method of the present invention has good accuracy.

[0039] Example 2

[0040] This embodiment is the same as embodiment 1 except for the following technical features: Step (1) the reaction temperature is set to 75°C, and the oil sample collected after the reaction for 120 minutes is the enzymatic esterification oil.

[0041] Through detection and calculation by the method described in Example 1, in the product obtained in this example, high melting point triglycerides account for 13.4%. According to the method of the present invention, the consistency of the plastic fat is improved, the ductility and viscosity are improved, and the plasticity is improved.

[0042] It has been verified that the viscosity of the product increased from the initial 103mpa·s to 630mpa·s, and the viscosity was improved; the SFC change trend of the product was more gentle, and the viscosity increased; the product crystallization was mainly β′ crystal form (the proportion increased from 16% to 78%), and the plasticity was improved. This is consistent with the conclusion of the present invention, indicating that the evaluation method of the present invention has good accuracy.

[0043] Example 3

[0044] This embodiment is the same as Embodiment 1 except for the following technical features: In step (1), the reaction temperature is set to 60° C., and the oil sample collected after the reaction for 120 min is the enzymatic esterification oil.

[0045] According to the detection and calculation method described in Example 1, the high melting point triglyceride in the product obtained in this example accounts for 16.0%. According to the method of the present invention, the consistency of the plastic fat is improved, the ductility and viscosity are improved, and the plasticity is improved.

[0046] It has been verified that the viscosity of the product increased from the initial 103mpa·s to 991mpa·s, and the viscosity was improved; the SFC change trend of the product was more gentle, and the consistency was improved; the product crystallization was mainly β′ crystal form (the proportion increased from 16% to 89%), and the plasticity was improved. This is consistent with the conclusion of the present invention, indicating that the evaluation method of the present invention has good accuracy.

[0047] Example 4

[0048] This embodiment is the same as Embodiment 1 except for the following technical features: Step (1) The amount of lipase added is 3%.

[0049] According to the detection and calculation method described in Example 1, the high melting point triglyceride in the product obtained in this example accounts for 13.3%. According to the method of the present invention, the consistency of the plastic fat is improved, the ductility and viscosity are improved, and the plasticity is improved.

[0050] It has been verified that the viscosity of the product increased from the initial 103mpa·s to 717mpa·s, and the viscosity was improved; the SFC change trend of the product was more gentle, and the viscosity increased; the product crystallization was mainly β′ crystal (the proportion increased from 16% to 81%), and the plasticity was improved. This is consistent with the conclusion of the present invention, indicating that the evaluation method of the present invention has good accuracy.

[0051] Example 5

[0052] This embodiment is the same as Embodiment 1 except for the following technical features: Step (1) The amount of lipase added is 10%.

[0053] Through detection and calculation by the method described in Example 1, in the product obtained in this example, high melting point triglycerides account for 14.1%. According to the method of the present invention, the consistency of the plastic fat is improved, the ductility and viscosity are improved, and the plasticity is improved.

[0054] It has been verified that the viscosity of the product increased from the initial 103mpa·s to 699mpa·s, and the viscosity was improved; the SFC change trend of the product was more gentle, and the viscosity increased; the product crystallization was mainly β′ crystal form (the proportion increased from 16% to 79%), and the plasticity became better. This is consistent with the conclusion of the present invention, indicating that the evaluation method of the present invention has good accuracy.

[0055] Example 6

[0056] This embodiment is the same as embodiment 1 except for the following technical features: Step (1) The lipase is Lipozyme RMIM with an addition amount of 5%.

[0057] Through detection and calculation by the method described in Example 1, in the product obtained in this example, high melting point triglycerides account for 15.2%. According to the method of the present invention, the consistency of the plastic fat is improved, the ductility and viscosity are improved, and the plasticity is improved.

[0058] It has been verified that the viscosity of the product increased from the initial 103mpa·s to 988mpa·s, and the viscosity was improved; the SFC change trend of the product was more gentle, and the viscosity increased; the product crystallization was mainly β′ crystal form (the proportion increased from 16% to 86%), and the plasticity was improved. This is consistent with the conclusion of the present invention, indicating that the evaluation method of the present invention has good accuracy.

[0059] Example 7

[0060] This embodiment is the same as the embodiment 1 except for the following technical features: the ratio of the two oils in the mixed oil in the embodiment 1 is changed to obtain 100 g of the mixed oil, which is heated, melted and mixed uniformly. The mixed sample has a lauric acid L content of 5.7%, a myristic acid M content of 2.8%, a palmitic acid P content of 35.0%, a stearic acid S content of 4.1%, and an oleic acid O content of 37.6%. Since the SFC of the two oils in the mixed oil at 40° C. is 0, no matter what ratio the two oils are mixed in, the SFC reduction rate (%) of the obtained mixed oil is close to 100%.

[0061] Through detection and calculation by the method described in Example 1, in the product obtained in this example, high melting point triglycerides account for 15.3%. According to the method of the present invention, the consistency of the plastic fat is improved, the ductility and viscosity are improved, and the plasticity is improved.

[0062] It has been verified that the viscosity of the product increased from the initial 112mpa·s to 705mpa·s, and the viscosity was improved; the SFC change trend of the product was more gentle, and the consistency was improved; the product crystallization was mainly β′ crystal form (the proportion increased from 9% to 81%), and the plasticity was improved. This is consistent with the conclusion of the present invention, indicating that the evaluation method of the present invention has good accuracy.

[0063] Example 8

[0064] This embodiment is the same as the embodiment 1 except for the following technical features: the ratio of the two oils in the mixed oil in the embodiment 1 is changed to obtain 100g of the mixed oil, which is heated, melted and mixed uniformly, and the content of lauric acid L in the mixed sample is 8.1%, the content of myristic acid M is 3.6%, the content of palmitic acid P is 35.9%, the content of stearic acid S is 4.3%, and the content of oleic acid O is 38.9%. Since the SFC of the two oils in the mixed oil at 40° C. is 0, no matter what ratio the two oils are mixed, the SFC reduction rate (%) of the obtained mixed oil is close to 100%.

[0065] Through detection and calculation by the method described in Example 1, in the product obtained in this example, high melting point triglycerides account for 17.8%. According to the method of the present invention, the consistency of the plastic fat is improved, the ductility and viscosity are improved, and the plasticity is improved.

[0066] It has been verified that the viscosity of the product increased from the initial 110mpa·s to 970mpa·s, the SFC change trend of the product became more gentle, and the viscosity increased; the product crystallization was mainly β′ crystal (the proportion increased from 11% to 85%), and the plasticity became better. This is consistent with the conclusion of the present invention, indicating that the evaluation method of the present invention has good accuracy.

[0067] Example 9

[0068] This embodiment is the same as Embodiment 1 except for the following technical features: the reaction temperature is set at 80° C., and the oil sample collected after the reaction for 120 minutes is the enzymatic transesterification oil.

[0069] Through detection and calculation by the method described in Example 1, in the product obtained in this example, high melting point triglycerides account for 12.1%. According to the method of the present invention, the consistency of the plastic fat is slightly improved, the ductile viscosity is reduced, and the plasticity is deteriorated.

[0070] It has been verified that the viscosity of the product slightly decreased from the initial 103mpa·s to 100mpa·s, and the ductile viscosity slightly decreased; the SFC of the product changed slightly more slowly, and the viscosity increased; but the product crystallization was still mainly β-crystal (the proportion decreased from 16% to 15%), and the plasticity became worse. This is consistent with the conclusion of the present invention, indicating that the evaluation method of the present invention has good accuracy.

[0071] Example 10

[0072] This embodiment is the same as Embodiment 1 except for the following technical features: the reaction temperature is set at 60°C, and the oil sample collected after the reaction for 30 minutes is the enzymatic esterification oil.

[0073] According to the detection and calculation method described in Example 1, in the product obtained in this example, high melting point triglycerides account for 11.5%. According to the method of the present invention, the consistency is slightly improved, the ductile viscosity is reduced, and the plasticity is deteriorated.

[0074] It has been verified that the viscosity of the product has slightly decreased from the initial 103mpa·s to 98mpa·s, and the ductile viscosity has slightly decreased; the SFC of the product has changed slightly more slowly, and the viscosity has slightly increased; but the product crystallization is still mainly β-crystalline (the proportion of β' has decreased from 16% to 11%), and the plasticity has deteriorated. This is consistent with the conclusion of the present invention, indicating that the evaluation method of the present invention has good accuracy.

[0075] Embodiment 11

[0076] This embodiment is the same as the embodiment 1 except for the following technical features: the ratio of the two oils in the mixed oil in the embodiment 1 is changed to obtain 100g of the mixed oil, which is heated, melted and mixed uniformly, and the content of lauric acid L in the mixed sample is 11.9%, the content of myristic acid M is 4.8%, the content of palmitic acid P is 31.9%, the content of stearic acid S is 3.9%, and the content of oleic acid O is 35.5%. Since the SFC of the two oils in the mixed oil at 40° C. is 0, no matter what ratio the two oils are mixed, the SFC reduction rate (%) of the obtained mixed oil is close to 100%.

[0077] According to the detection and calculation method described in Example 1, in the product obtained in this example, high melting point triglycerides account for 8.6%. According to the method of the present invention, the consistency is slightly improved, the ductile viscosity is reduced, and the plasticity is deteriorated.

[0078] It has been verified that the viscosity of the product slightly decreased from the initial 118mpa·s to 112mpa·s, and the ductile viscosity decreased; the SFC of the product changed slightly more slowly, and the viscosity slightly increased; but the product crystallization was still mainly β-crystalline (β' proportion decreased from 18.5% to 18%), and the plasticity became worse. This is consistent with the conclusion of the present invention, indicating that the evaluation method of the present invention has good accuracy.

[0079] Example 12

[0080] This embodiment is the same as the embodiment 1 except for the following technical features: the ratio of the two oils in the mixed oil in the embodiment 1 is changed to obtain 100g of the mixed oil, which is heated, melted and mixed uniformly, and the content of lauric acid L in the mixed sample is 28.6%, the content of myristic acid M is 10.2%, the content of palmitic acid P is 21.4%, the content of stearic acid S is 2.8%, and the content of oleic acid O is 26.5%. Since the SFC of the two oils in the mixed oil at 40° C. is 0, no matter what ratio the two oils are mixed, the SFC reduction rate (%) of the obtained mixed oil is close to 100%.

[0081] According to the detection and calculation method described in Example 1, in the product obtained in this example, high melting point triglycerides account for 7.4%. According to the method of the present invention, the consistency is slightly improved, the ductile viscosity is reduced, and the plasticity is deteriorated.

[0082] It has been verified that the viscosity of the product slightly decreased from the initial 130mpa·s to 118mpa·s, and the ductile viscosity decreased; the SFC of the product changed slightly, and the viscosity slightly increased; but the product crystallization was still mainly β-crystalline (the proportion of β' decreased from 21% to 20%), and the plasticity became worse. This is consistent with the conclusion of the present invention, indicating that the evaluation method of the present invention has good accuracy.

[0083] Example 13

[0084] This embodiment is the same as the embodiment 1 except for the following technical features: the ratio of the two oils in the mixed oil in the embodiment 1 is changed to obtain 100g of the mixed oil, which is heated, melted and mixed uniformly, and the content of lauric acid L in the mixed sample is 2.3%, the content of myristic acid M is 1.7%, the content of palmitic acid P is 38.0%, the content of stearic acid S is 4.5%, and the content of oleic acid O is 40.7%. Since the SFC of the two oils in the mixed oil at 40° C. is 0, no matter what ratio the two oils are mixed, the SFC reduction rate (%) of the obtained mixed oil is close to 100%.

[0085] According to the detection and calculation method described in Example 1, in the product obtained in this example, high melting point triglycerides account for 18.3%. According to the method of the present invention, the consistency is improved, the ductile viscosity is reduced, and the plasticity is deteriorated.

[0086] It has been verified that the viscosity of the product is reduced from the initial 121mpa·s to 98mpa·s, and the ductile viscosity is reduced; the SFC of the product changes smoothly, and the viscosity is slightly improved; but the product crystallization is still mainly β-crystalline (the proportion of β' is reduced from 25% to 22%), and the plasticity is deteriorated. This is consistent with the conclusion of the present invention, indicating that the evaluation method of the present invention has good accuracy.

[0087] Embodiment 14

[0088] This embodiment is the same as the embodiment 1 except for the following technical features: the ratio of the two oils in the mixed oil in the embodiment 1 is changed to obtain 100g of the mixed oil, which is heated, melted and mixed uniformly, and the content of lauric acid L in the mixed sample is 3.3%, the content of myristic acid M is 2.5%, the content of palmitic acid P is 39.3%, the content of stearic acid S is 4.9%, and the content of oleic acid O is 32.3%. Since the SFC of the two oils in the mixed oil at 40° C. is 0, no matter what ratio the two oils are mixed, the SFC reduction rate (%) of the obtained mixed oil is close to 100%.

[0089] According to the detection and calculation method described in Example 1, in the product obtained in this example, high melting point triglycerides account for 19.5%. According to the method of the present invention, the consistency is improved and the ductile viscosity is reduced.

[0090] It has been verified that the viscosity of the product is reduced from the initial 131mpa·s to 110mpa·s, the viscosity is reduced, the SFC of the product changes smoothly, and the consistency is improved; however, the product crystallization is still mainly β-crystalline (the proportion of β' is reduced from 29% to 28%), and the plasticity is deteriorated. This is consistent with the conclusion of the present invention, indicating that the evaluation method of the present invention has good accuracy.

[0091] Table 1 is the SFC variation data of the product of the embodiment. The details are as follows:

[0092] Table 1 SFC change data of the products of the examples

[0093] 10℃ 20℃ 25℃ 30℃ 35℃ 40℃ Example 1 35.2 22 15.7 11.9 10.4 8.5 Example 2 39.3 24.2 16.8 11.8 9.9 8.47 Example 3 38.2 21.2 15.9 12 8.8 7.5 Example 4 37.9 22.5 16 12.02 10.9 7.7 Example 5 36.6 23.4 17.5 13.2 11 8.6 Example 6 37.1 22.9 17 12.5 10.5 8.5 Example 7 40.1 25.6 20.1 13.2 11.2 7.9 Example 8 37.7 25.3 18.4 15.2 12.3 10 Example 9 36.6 21.3 13.5 9.8 8.5 3.2 Example 10 21.23 9.8 6.26 3.35 1.4 0.89 Embodiment 11 38.7 19.8 12.6 5.8 2.8 1.1 Example 12 42.1 21.5 10.8 6.4 1.9 0.2 Example 13 43.4 29.1 19.2 15.3 11.8 10.6 Embodiment 14 43.1 26.4 20.3 15.6 13.8 11.9

[0094] Table 2 shows the viscosity changes of the products of the examples. The details are as follows:

[0095] Table 2

[0096] β′ ratio (%) Viscosity(mpa.s) Example 1 85 968 Example 2 78 630 Example 3 89 991 Example 4 81 717 Example 5 79 699 Example 6 86 988 Example 7 81 705 Example 8 85 970 Example 9 15 100 Example 10 11 98 Embodiment 11 18 112 Example 12 20 118 Example 13 22 98 Embodiment 14 28 110

[0097] Table 3 shows the changes in triglyceride composition of the products of the examples. The details are as follows:

[0098] Table 3

[0099]

[0100] Table 4 shows the percentage (%) of high melting point triglycerides in the products of the examples, as follows:

[0101] Table 4

[0102] High melting point triglyceride ratio (%) Example 1 15.3 Example 2 13.4 Example 3 16 Example 4 13.3 Example 5 14.1 Example 6 15.2 Example 7 15.3 Example 8 17.8 Example 9 12.1 Example 10 11.5 Embodiment 11 8.6 Example 12 7.4 Example 13 18.3 Embodiment 14 19.5

[0103] Conclusion: By testing the proportion of high melting point triglycerides in the product, it is possible to predict the changes in the consistency and ductility of the SFC curve of the product, and then evaluate the changes in the plasticity of the oil product. If the proportion of high melting point triglycerides in the product is controlled at 13-18%, it means that the consistency and ductility of the product are improved, and the plasticity is improved; if the proportion is less than 13%, the consistency of the product is slightly improved, the ductility and viscosity decrease, and the plasticity is worse; if the proportion is greater than 18%, it means that the consistency of the product is improved, the ductility and viscosity decrease, and the plasticity is poor.

[0104] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications made without departing from the spirit and principles of the present invention shall be equivalent replacement methods and shall be included in the protection scope of the present invention.

Claims

1. A method for evaluating the plasticity of plastic fat, characterized in that The following steps are involved: (1) adding an enzyme catalyst to the mixed oil and fat, setting the reaction temperature and performing transesterification modification; (2) monitoring the content of medium melting point triglycerides and high melting point triglycerides in the system, calculating the percentage of the total amount of high melting point triglycerides to the total amount of medium melting point and high melting point triglycerides, and reflecting the changes in consistency, viscosity and plasticity of the plastic fat through the numerical change rate; In step (2), when the total amount of high-melting-point triglycerides accounts for 13-18% of the total amount of medium-melting-point triglycerides and high-melting-point triglycerides, it means that the obtained plastic fat has improved ductility and viscosity, improved consistency, and better plasticity compared with the mixed oil before modification; when the total amount of high-melting-point triglycerides accounts for less than 13% or greater than 18% of the total amount of medium-melting-point triglycerides and high-melting-point triglycerides, it means that the obtained plastic fat has improved consistency, reduced ductility and viscosity, and worse plasticity.

2. The method for evaluating the plasticity of plastic fat according to claim 1, characterized in that: The mixed oil in step (1) is obtained by mixing an oil rich in lauric acid C12:0 and myristic acid C14:0 with an oil rich in palmitic acid C16:0, stearic acid C18:0 and oleic acid C18:1; the mixed oil must contain these five fatty acids.

3. The method for evaluating the plasticity of plastic fat according to claim 2, characterized in that: The mass percentage of lauric acid L in the mixed oil described in step (1) is 1-28.6%, the mass percentage of myristic acid M is 1-10.2%, the mass percentage of palmitic acid P is 21.4-45%, the mass percentage of stearic acid S is 1-5%, and the mass percentage of oleic acid O is 26.5-40.7%, wherein the mass percentage refers to the percentage of the corresponding fatty acids in the total mass of the mixed oil after the mixed oil is completely hydrolyzed.

4. The method for evaluating the plasticity of plastic fat according to claim 2, characterized in that: The mass percentage of lauric acid L in the oil described in step (1) is 5.7-9.5%, the mass percentage of myristic acid M is 2.8-7.1%, the mass percentage of palmitic acid P is 34.5-35.9%, the mass percentage of stearic acid S is 3.5-4.3%, and the mass percentage of oleic acid O is 36.2-38.9%, wherein the mass percentage refers to the percentage of the corresponding fatty acids in the total mass of the mixed oil after the mixed oil is completely hydrolyzed.

5. The method for evaluating the plasticity of plastic fat according to claim 1, characterized in that: The enzyme catalyst in step (1) is low-temperature lipase.

6. The method for evaluating the plasticity of plastic fat according to claim 1, characterized in that: The enzyme catalyst in step (1) is one of lipase Lipozyme TL IM and lipase Lipozyme RMIM.

7. The method for evaluating the plasticity of plastic fat according to claim 1, characterized in that: The amount of the enzyme catalyst added in step (1) is 3-10% of the mass of the mixed oil.

8. The method for evaluating the plasticity of plastic fat according to claim 1, characterized in that: The temperature of the transesterification reaction in step (1) is 60-80° C., and the reaction time is 30-120 min.

9. The method for evaluating the plasticity of plastic fat according to claim 1, characterized in that: The high melting point triglycerides described in step (2) are PPP and PPS type triglycerides, and the medium melting point triglycerides are triglycerides with a total carbon number below C46, ​​MPP and MOM type triglycerides.

10. The method for evaluating the plasticity of plastic fat according to claim 1, characterized in that: When the total amount of high melting point triglycerides accounts for more than 18% of the total amount of medium melting point and high melting point triglycerides, the consistency is improved more than when the total amount of high melting point triglycerides accounts for less than 13% of the total amount of medium melting point and high melting point triglycerides.

Citation Information

Patent Citations

  • Frying oil quality fast-evaluation method and device

    CN106370560A

  • Oil and fat composition and plastic oil and fat composition

    JP5421496B1